Brasil de todos os cantos: programas radiofônicos musicais do Projeto Minerva pelo radialista J. da Silva Vidal na Rádio Bandeirantes de São Paulo - Cibele Lauria Silva (2011)
This work proposes to analyze, by the historical, political and musical context, eleven musical and educational radio programs, transmitted through the cultural newsletter, part of the extinct Project Minerva, called Brasil de todos os Cantos. They were broadcast by Radio Bandeirantes of Sao Paulo in the seventies and eighties. The broadcaster José da Silva Vidal has a dynamic history in the cultural-radiophonic scenario, being responsible for producing, searching and presenting a part of this programs. For such, he had utilized his particular music collection of vinyl discs and tapes, always emphasizing what he considers as brazilian authentic music. For making an analysis of these programs, were used interdisciplinary theories of the areas of communication, history of Brazilian popular music, anthropology and ethnomusicology. The research with the broadcaster and his collection, has consisted firstly in a historical-documental analysis, with the transcriptions of tapes containing programs demonstrations of the extinct Project Minerva. The ethnography mainly occurred in the listening of programs, made in the presence of the broadcaster, using the technique of oral history. The Project Minerva was a project of the federal government shown in the whole country, proposing a model of distance education, interfering directly in the history of education, in the culture and in the disseminate identity in the programs. The analysis of the repertoire, which honors some composers and musical styles, but omitting others, shows us how and what it has influenced the cultural market since the early history of radio, on the concept of "true Brazilian popular music" to the listeners of all over the country.